PRODUCT INNOVATION, DIGITAL MARKETING, BRAND IMAGE, AND COMPETITIVE ADVANTAGE OF ENDEK CRAFT SMES IN BADUNG REGENCY: A DESCRIPTIVE ANALYSIS - Ni Nyoman Kerti Yasa; I Putu Gde Sukaatmadja; Ni Wayan Ekawati; Putu Laksmita Dewi Rahamayanti (Adisam Publisher, 2026)
The purpose of this study is to explain product innovation, digital marketing, brand image, and competitive advantage of Endek craft SMEs in Badung Regency. The population of this research consists of business actors engaged in Endek craft SMEs in Badung Regency. The sample size used in this study was 112 Endek craft SME business actors, selected using purposive sampling. The analytical technique employed was descriptive analysis. The results show that product innovation implemented by Endek craft SMEs in Badung Regency falls into the very high category. Likewise, the application of digital marketing is also categorized as very good. The brand image of Endek crafts is classified as good, while their competitive advantage is considered very high. Therefore, it is essential for Endek craft SME business actors in Badung Regency to consistently innovate their products and implement digital marketing strategies to sustain and strengthen their brand image and competitive advantage.